The Effect of Teachers’ Self-Efficacy and Creativity on English as a Foreign Language Learners’ Academic Achievement - Ma, Yuanyuan (Frontiers in Psychology, 2022)
Since learners’ academic achievement is the ultimate goal of any system of education, multitudes of studies have been conducted on this variable and its determinants. That is, several scholars have explored the effects of student-related and teacher-related factors on learners’ academic achievement. Notwithstanding, a few researchers have investigated the effects of teachers’ self-efficacy and creativity on learners’ academic achievement. Furthermore, no study has reviewed the role of these teacher-related factors in learners’ achievement. Therefore, the present study seeks to bridge the lacunas by delving into the influence of teachers’ self-efficacy and creativity on EFL learners’ academic achievement. The beneficial effects of self-efficacy beliefs and creative teaching were outlined through the existing evidence. This seems to be illuminative for EFL teachers. Given the positive consequences of teachers’ self-efficacy for students’ achievement, EFL teachers should believe in themselves and their abilities to lead their students to academic success. Additionally, with regard to the positive impact of teachers’ creativity on learners’ achievement, EFL teachers are expected to teach the course content creatively.